Jordan : 2020 Article IV Consultation and Request for an Extended Arrangement under the Extended Fund Facility-Press Releases; Staff Report; and Statement by the Alternate Executive Director for Jordan. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Jordan's 2020 Article IV Consultation and Request for an Extended Arrangement Under the Extended Fund Facility (ECF). Jordan's IMF-supported economic reform program is anchored on structural reforms designed to spur growth by creating jobs-especially for women and young people-and reduce poverty. The Jordanian economy has continued facing significant challenges. Macroeconomic stability and external buffers have been preserved, but fiscal vulnerabilities remain. Structural reforms and continued fiscal consolidation efforts are critical to lift growth, reduce unemployment and bring debt on a downward path. Continued support from donors, particularly through concessional loans and budget grants, will be critical to help Jordan cope with humanitarian and economic needs. The coronavirus disease 2019 (COVID-19) outbreak poses significant risks to the program implementation. The authorities have implemented measures to help contain the impact of the pandemic; however, adjustments to the program modalities might be necessary considering the rapidly changing circumstances. Donor support through budget grants and concessional financing will be critical to help Jordan cope with the effects of the COVID-19 outbreak and the Syrian refugee crisis and to support program objectives.